Filamentous Bacterial Viruses V. Asymmetric Replication of fd Duplex Deoxyribonucleic Acid - Tseng, B. Y. (1972)
Short pulses (30 sec at 32 C) of (3)H-thymidine were found primarily in the viral strands of replicating fd deoxyribonucleic acid (DNA), even at a time when most DNA being synthesized was duplex DNA. Much of the labeled viral strand DNA was longer than unit length, but some was shorter than unit length. Most of the corresponding complementary-strand DNA was recovered in closed supercoiled duplex molecules, even for short pulses; the remainder of the complementary-strand DNA was found in replicative intermediates in pieces shorter than unit length. Some of the viral strands in open replicating DNA lacked a corresponding complementary strand.